MODUL FAKTOR YANG DIBENTUK DARI SUBMODUL Z^2 PADA MODUL R^2 ATAS GAUSSIAN INTEGERS - Ari Wardayani (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2012)
We prove that ℝ2 is module over Gaussian Intergers and the set of all coset of submodule in module ℝ2 over Gaussian Integers is a quotient module. We find the proof by showing that ℝ2 is both a right module and a left module over Gaussian Integers and showing that the set of all coset of submodule in module ℝ2 is both a right module and a left module over Gaussian Integers.